A green approach of utilising Banana peel (Musa paradisiaca) as adsorbent precursor for an Anionic dye removal: kinetic, isotherm and thermodynamics analysis - Basirun, Ain Aqilah; Othman, Ahmad Razi; Yasid, Nur Adeela; Shukor, Mohd Yunus Abd; Khayat, Mohd Ezuan (Multidisciplinary Digital Publishing Institute, 2023)
Methods for removing pollutants include membrane isolation, ion exchange, precipitation, transformation, and biosorption. Adsorption is a cost-effective method of treating industrial wastewater and a common commercial method for concentrating valuable molecules or eliminating contaminants. Banana peel is one of the largest underutilized agricultural wastes in Malaysia. A novel method of using a low-cost biosorbent made from banana peel and Evans blue (EB) dye as a target is the target of this study. The optimal conditions for EB dye adsorption occurred at a dye concentration of 200 mg/L, adsorbent dosages between 10 and 20 g/L, temperature of 25 °C, incubation time of 180 min, and agitation speeds of 100 rpm. Statistical discriminatory analysis showed that the pseudo-second-order kinetic model and the Redlich“Petersen isotherm model were the best models. The maximum adsorption capacity based on Langmuirs isotherm prediction was 58.51 mg gˆ’1. A non“linear regression of the thermodynamic vant Hoff plot based on a dimensionless equilibrium constant resulted in negative values for Gibbs free energy and enthalpy, indicating that the adsorption process is spontaneous and exothermic.